Humor as a pedagogical strategy: a short review - Vasconcelos, Silvia Ines Coneglian Carrilho de; Dellai, Érica Milani (Revista Letras Raras, 2021)
Several theoretical research works discuss teachers´ pedagogical practices, among which there are frequentin timations of lack of students´ concentration and stimulation in the classroom. They are mostly the cause and consequence of boring lessons which do not yield results as from the contents of the subject matter developed. Educators strive for new methods for more agreeable and dynamic lessons. Humor may be one of the strategies that has been discussed and analyzed. However, humor is still a cause of discussions due to several issues involved and to the mode it is addressed within the classroom. A bibliographic survey has been developed to approach the use of humor in the classroom. Research comprised the contribution of authors (ABU BAKAR, 2018; BENEDICTO, 2013; ENGRÁCIO, 2008; JOSÉ, 2008; MARLOW, 2017; OTTONI, 2007; SANTOS, 2010; SOUSA, 2016) who studied the theme, its problems and applicability within the different disciplines to have a general view on the matter and which may foreground further research. It has been observed during the process that the strategy, if worked out properly, is beneficent for bonding between student and teacher, efficient learning, letting off steam within the classroom. It is also highly appreciated by students. Care must be taken not to go beyond the limits in pedagogical activities.